A FORMAÇÃO PARA O MINISTÉRIO PASTORAL: PERCEPÇÕES DE PASTORAS METODISTAS - OLIVEIRA, ANDREIA FERNANDES (2018)
This thesis aims to identify the perceptions of women in the practice of pastoral ministry who graduated from the School of Theology of the Methodist Church. Based on the assumptions of critically thinking authors in various areas of social, theological and educational studies, the theoretical basis of this research is composed from thinkers who, when discussing relationships between men and women, which are marked by the imposition of hegemonic values, such as colonization, masculinization and whitening of knowledge, make it evident that education can be an instrument toward the reproduction of these values. In this sense, the theological formation for the practice of the pastoral ministry has been influenced by these values. Concepts of theological education, pastoral ministry, intersectionality, and problematizing education are part of this critical dialogue among bibliographic sources. As a methodological field instrument, the focus group included female pastors in ministerial practice, who all studied and graduated from the School of Theology of the Methodist University of São Paulo at different times. From the analysis of the data, the hypothesis was confirmed that the theological formation of the School of Theology of the Methodist Church is masculinized and masculinizing, established mainly by men and for men. It is therefore necessary to transform the space of theological formation and clerical space. It is necessary to build places for reflection and encouragement of actions that confront the church in relation to practices of discrimination and rejection of women in the exercise of pastoral ministry.